Marguerite Poland and the Shades Archive: The Use of the Author s Archive in Close Analysis - Webster, Emily (Department of English Language and Literature, 2025)
Marguerite Poland's Shades combines the histories of South Africa's Eastern Cape and her own missionary ancestors to create a novel which utilises fictionality for postcolonial criticism and a search for identity. Shades is therefore deeply situated within the historical archive on which the text leans heavily to provide credibility to the semi-fictional historical narrative. However, a closer examination of Poland's research points towards the existence of a cache of information which informed the writing of her text. This thesis has consequently termed this concept the ‘author's archive'. When the author's archive is examined in conjunction with Shades, a deeper understanding and far stronger analysis emerges – resulting in authoritative conclusions rather than speculation. The purpose of this thesis is ultimately to introduce the theoretical concept of an author removing and manipulating material from the archive with the intention of constructing their own archive of sources. Because of the focus on the creation of a theoretical framework, a theoretical rather than methodological approach is most suited. This thesis has therefore sought to construct and define a theory to examine the relationship between the auctorial and the archival rather than create and apply a method of analysis. Poland's Shades presents itself as an ideal case study due to Poland's intentional and obvious employment of the archive. Firstly, her adaptation and subsequent utilisation of intermingled archival fact and original fiction prompts an investigation of what led Poland to select specific material from the archive. Secondly, Poland's characters are predominantly based on fact. Many were inspired by the oral and written history of her missionary ancestors, which she in turn adapts and subverts through fictionalisation to suit her narrative. An analysis of these characters provides an opportunity to examine Poland's interweaving of historical versus imaginative due to their varying range of fictionality. The reconstruction and examination of the archive Poland created for Shades has undoubtedly led to a substantial analysis of Shades and Poland's creation of the text. However, a conclusion has also been reached that analysing the author's archive reveals how fiction can be supported by fact rather than fact simply supported by fiction, and how this can lead to the emergence of an accreditable historical narrative.